(untitled) (ACME, 2021)
In my research I deepened the tόpos of the tyrant defeated by divine justice within an apologetic text attributed to the rhetorician Lucius Caecilius Firmianus Lactantius, the De mortibus persecutorum. It is a little known work, on which little has been written and investigated. With this work I propose to analyze, explain and comment on the author’s angry victory song. A Christian imbued with classical culture and an exciting storyteller, who through Tacitian essential prose describes the heart-rending and painful deaths suffered by those among the Roman emperors who have become protagonists of violent anti-Christian persecutions. In obedience to a providential design, the principes will find themselves victims of their own cruelty and their own vitia, for which they will suffer the just divine punishment; the penalties will be commensurated with the inhumanity of the sins committed by them. From an historical-political point of view, the work fits perfectly into Constantinian propaganda: Costantino himself is presented, in fact, as a tolerant princeps enlightened by the transcendent justice of God, in a process of Christianization of the theology of Roman victory. He alone will be able to overthrow an anti-Christian tyrannical government to give the world what Lactantius calls a pax iucunda et serena with smug hyperbole.